2016
DOI: 10.2139/ssrn.2835536
|View full text |Cite
|
Sign up to set email alerts
|

Is Partisan Alignment Electorally Rewarding? Evidence from Village Council Elections in India

Abstract: Is Partisan Alignment Electorally Rewarding? Evidence from Village Council Elections in India *Do ruling parties positively discriminate in favour of their own constituencies in allocating public resources? If they do, do they gain electorally in engaging in such a practice? This paper tests whether partisan alignment exists in the allocation of funds for India's largest social protection programme, the National Rural Employment Guarantee Scheme (NREGS) in the state of West Bengal in India, and whether incumbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Our result that effect of political competition on allocation of private benefits is heterogeneous across politically aligned and non-aligned regions is consistent with evidence found in Dey and Sen (2016) and Gupta and Mukhopadhyay (2016). These authors examine the manipulation of funds by state and district officials for electoral advantage under the MGN-REGA 4 , a welfare program providing employment.…”
Section: Related Literaturesupporting
confidence: 87%
“…Our result that effect of political competition on allocation of private benefits is heterogeneous across politically aligned and non-aligned regions is consistent with evidence found in Dey and Sen (2016) and Gupta and Mukhopadhyay (2016). These authors examine the manipulation of funds by state and district officials for electoral advantage under the MGN-REGA 4 , a welfare program providing employment.…”
Section: Related Literaturesupporting
confidence: 87%
“…The paper contributes to the growing literature on political alignment between different layers of government. The main results are in line with previous literature showing that political alignment influences subnational transfers and subsequent elections (Ade and Freier, 2013;Arulampalam et al, 2009;Borcan, 2016;Bracco et al, 2015;Brollo and Nannicini, 2012;Dey and Sen, 2016;Levitt and Snyder Jr., 1997;Solé-Ollé and Sorribas-Navarro, 2008). This is one of the few papers focusing in a context of weak parties.…”
Section: Introductionsupporting
confidence: 91%
“…This can happen because local and national officers have a symbiotic relationship, in which they exchange transfers and control over local policy for votes and legislative support. In a broader context, abundant evidence has shown that political alignment siginficantly affects subnational transfers and electoral results in both developed and developing countries (Ade and Freier, 2013;Arulampalam et al, 2009;Borcan, 2016;Bracco et al, 2015;Brollo and Nannicini, 2012;Dey and Sen, 2016;Levitt and Snyder Jr., 1997;Solé-Ollé and Sorribas-Navarro, 2008). While most of these studies are based on countries in which the center-periphery negotiation is mediated by relatively strong parties, less is known about alignment effects when the party system is weak.…”
Section: Introductionmentioning
confidence: 99%
“…11 There is considerable evidence that local governments in West Bengal direct benefits towards swing voters (Bardhan et al 2015;Dey and Sen 2016).…”
Section: Empirical Context and Intervention Designmentioning
confidence: 99%
“…Despite the promise that decentralization can improve targeting and implementation through better information and accountability, a growing literature argues that these programs have a mixed record. 1 Community-led programs are often captured by the local elite (see, for example World Development Report 2004; Mansuri and Rao 2013;Vera-Cossio 2018;Deserranno et al 2018), and there is evidence that local governments target their vote bank, rather than those who stand to benefit the most (Stokes 2005;Robinson and Verdier 2013;Bardhan et al 2015; Bardhan and Mookherjee 2016;Devarajan and Khemani 2016;Dey and Sen 2016).…”
Section: Introductionmentioning
confidence: 99%